Problem-Oriented Learning as a Method of Developing Soft Skills Among Students of Pedagogical Specialties - Perizat Sanatbay; Guldana Smailova; Kadisha Shalgynbayeva; Marziya Asilbekova; Anar Tauekelova (Education Sciences)
In the context of the transformation of the modern higher education system, the supra-professional competencies (soft skills) necessary for future specialists in the humanitarian field, in particular, social educators, are of particular importance. The present study is aimed at studying the effectiveness of problem-based learning (PBL) as a method of forming key soft skills among students of the educational program “Social Pedagogy” of the L.N. Gumilyov Eurasian National University. The theoretical part of the study includes an overview of international and domestic scientific discourse on flexible skills and a problem-oriented approach. In the empirical part, the methods of pedagogical experimentation, questionnaires, self-assessment of competencies, and quantitative analysis of the dynamics of soft skill development during the semester were applied. The results indicate a positive correlation between the intensity of students’ participation in PBL practices and the level of development of skills such as critical thinking, teamwork, communicative competence, and time management. The study also identified institutional and methodological barriers to the implementation of PBL in Kazakhstan’s educational practice, including the lack of trained facilitators and the lack of adapted cases. Based on the data obtained, a model of a localized PBL strategy integrated into the training of social educators is proposed. The research contributes to the development of the methodological culture of teacher education and opens up prospects for creating a sustainable system of soft skills formation in universities in Kazakhstan.